Examining Mathematics Achievement: An Analysis of Fourth and Eighth Grade TIMSS U.S. Data by Ethnicity, Gender, and Sociocultural Variables - Moon, Chi Yun; Larke, Patricia; James, Marlon (Journal of Ethnic and Cultural Studies, 2022)
Previous research studies about mathematics performance have continuously reported race/ethnic or gender gaps. Learners have different educational experiences depending on not only their ethnicity or gender, but also grade and sociocultural factors. However, only a few studies have considered all these factors integrally. Hence, the need of examining academic performance differences across ethnicity, gender, grade, and sociocultural variables led this study. The purpose of this study was to examine mathematics academic achievement of 4th and 8th grade African, Latinx, and Asian American students related to students’ ethnicity, gender, grade, and sociocultural variables such as student bullying, parental involvement, and engaging teaching. The guiding research question for this inquire was: Which factors (gender, student bullying, parental involvement, and engaging teaching) do predict the mathematics achievement of 4th and 8th grade African, Latinx, and Asian American students? The participants were total 9,605 fourth (n=4,785) and eighth grade (n=4,820) African, Latinx, and Asian American students in TIMSS 2015 U.S. national public-use data set. According to the results of multiple linear regression analyses, parental involvement was a significant predictor for all students across grade and ethnicity. In addition, engaging teaching from mathematics teachers significantly predicted 4th and 8th grade Latinx American students’ mathematics achievement. This study revealed that gender, student bullying, parental involvement, and engaging teaching had different level of impacts on mathematics achievement of each group of students.